THE QUESTIONS USED BY THE NON-ENGLISH TEACHERS AND THE STUDENTS' RESPONSES - Elvi Titik Ziah S. (Education : Jurnal Sosial Humaniora dan Pendidikan, 2021)
This study addresses three major problems: (1) Which type(s) of questions are asked by the teachers to the students at Tunas Harapan Vocational senior High School of Pati? (2)What levels of questions are related in those types of questions? (3)How effective are the questions given by the teachers? The qualitative approach was used to explore the implementation of teachers’ questions. Afterwards, the students’ responses were analysed to describe the interaction between them and teachers. The subjects of this study were the Math, Chemistry and welding teachers and the machine department students. Each teacher was recorded during the teaching and learning process. The result shows that they more frequently used the divergent questions to encourage students to give responses and require students to engange in higher level cognition. They dominantly used lower levels of cognition such as understanding and applying. Referring to the students’ responses it could be categorized that the questions given by the teachers were effective for the students since more than 50% of the students answered “yes” from the questionnaire given, supported with the rubric of NYSUT’s Teacher Practice.